Association between passive stiffness of hamstring and eccentric knee flexion angle-torque relationship - Satoru Nishida; Shun Kunugi; Kiyoshi Maehara; Shumpei Miyakawa (Japanese Society of Physical Fitness and Sports Medicine, 2021)
Larger hip flexion range of motion with knee extension (hip flexion ROM) and passive stiffness of the hamstring is associated with greater production of isometric and concentric knee flexion torque at longer muscle lengths. Nevertheless, associations among hip flexion ROM, passive stiffness of hamstring, and eccentric knee flexion torque at a longer muscle length remain unclear. Therefore, we aimed to investigate the association among hip flexion ROM, passive stiffness of hamstring and eccentric knee flexion angle-torque relationship. Seventeen healthy male college students participated in this study, and all measurements were performed on both legs (34 legs). No participants had any previous hamstring strain injury. Hip flexion ROM, passive stiffness of hamstring, peak torque and peak torque angle during isokinetic eccentric knee flexion were measured. The correlation among the variables of interest were assessed. Passive stiffness of hamstring and eccentric peak knee flexion torque negatively correlated with the peak torque angle (r = −0.39). On the other hand, peak torque angle was not correlated with hip flexion ROM (r = 0.08). The present study revealed that higher passive stiffness of hamstring was associated with greater production of eccentric knee flexion torque at longer muscle lengths.